Whole-genome sequence assembly of the water buffalo (Bubalus bubalis) - Tantia, M S; Vijh, R K; Bhasin, V; Sikka, Poonam; Vij, P K; Kataria, R S; Mishra, B P; Yadav, S P; Pandey, A K; Sethi, R K; Joshi, B K; Gupta, S C; et al. (The Indian Journal of Animal Sciences, 2011)
The buffalo is an integral part of agriculture, particularly within the continent of Asia, providing a source of milk, meat, skin, hides, fertilizer, fuel, and draft power. The efficiency of this animal, compared to that of cattle, is higher in this region, though little is known about genome sequence of buffalo. The first version of assembly of a single female Murrah buffalo was constructed with Illumina paired end and mate pair short read sequencing using the cattle genome (Btau 4.0 assembly) as a reference. The assembly has read depth of 17-19X. The buffalo assembly represents ~ 91%-95% coverage in comparison to the cattle assembly Btau 4.0. The assembly has 185,150 contigs with the median contig length of 2.3 Kb and the largest contig length of 663 Kb. The mitochondrial genome is fully covered by a single contig. Whole genome comparison between this assembly and of cattle revealed 52 million mismatches/indels. The present analysis also unveils about 300 structural variants in the buffalo genome. The buffalo assembly has been integrated into a publically available genome browser with tracks for read pair insert distances, read depth, nucleotide variations, coverage, and the availability of custom tracks for scientific community. This assembly of the Water Buffalo is the first deep sequencing project that provides the resources to better understand the genomic basis of adaptable traits and genetic variation that distinguishes buffalo from cattle.